UrbanFoodplus – African-German Partnership to enhance resource use efficiency in urban and peri-urban agriculture for improved food security in West African cities - Buerkert, Andreas; Marschner, B.; Steiner, C.; Schlecht, Eva; Wichern, M.; Schareika, N.; Lowenstein, W.; Drescher, A.W.; Glaser, R.; Kranjac-Berisavljevic, Gordana; Gnankambary, Z.; Drechsel, Pay; et al. (2015)
Food security in West Africa not only depends on productivity increases in marginal rural areas, but also on enhanced use of intensively farmed agricultural “niche” lands such as the urban and peri-urban spaces. They are characterised by easy market access and input availability which allows self-reinforcing processes of agricultural intensification. However, too little is known about resource use efficiencies, matter flows and negative externalities in these systems. Starting from general assessments (status quo analyses), the African-German UrbanFoodPlus (UFP) network develops and tests site-specific, farmer-tailored innovations. These directly address the above mentioned knowledge gaps in the fourWest African cities of Ouagadougou (Burkina Faso), Tamale (Ghana), Bamako (Mali), and Bamenda (Cameroon). At all locations farmers attempt to cope with increasing land pressure by cultivating along electrical power lines, on public property, and on undeveloped private land.